The effectiveness of internal rhythm in the poetry of Ridicule with Ibin Bassam al-Bagdadi - علاء جاسم جابر سلمى كاظم نمر (College of Education for Women, 2019)
This study seeks to uncover the aesthetics of the internal rhythm and its effectiveness in enriching the poetic text with the music tone at represented in the art of repetition and the permit and recycling division and put back on the chest and the naturalization interview and counterpoint. And try to stand on the impact of internal rhythm to highlight the meaning of spelling and irony with poet Ibn Bassam Al-Bagdadi and have a close look at the literary and psychological motivations that led the poet to employ these colors in his ridicule and the extent of its contribution to intensify the poetic alphabetic flush. And deepening the meanings and provide poetic text in different aesthetics, there is no doubt that the old and modern Arabic poem and has focused to install its internal rhythm and justify reclining on it as phonetic stand to feel hearing with harmony and compatibility and acceptance.